The Research of Foreign Exchange Exposures in Taiwan - Chen, Yi Chen (2006)
The research will be mainly focused on the relationship between the stock returns and the fluctuation of foreign exchange rate exposure in Taiwan listed corporations. Due to the environmental limitations and in sufficient resources, if Taiwan inclines to develop international trade, the exchange market plays an important role in the advances of Taiwan's economy. Therefore, the fluctuations of foreign exchange rate must have a substantially impact on the profitability of industries in Taiwan.